1) 9 - 2 · (-4х + 7) = 7
2 · (-4х + 7) = 9 - 7
2 · (-4х + 7) = 2
-4х + 7 = 2 : 2
-4х + 7 = 1
-4х = 1 - 7
-4х = -6
х = -6 : (-4)
х = 1,5
Проверка: 9 - 2 · (-4 · 1,5 + 7) = 7
9 - 2 · (-6 + 7) = 7
9 - 2 · 1 = 7
7 = 7
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
2) 9 + 10 · (3х - 10) = 2
10 · (3х - 10) = 2 - 9
10 · (3х - 10) = -7
3х - 10 = -7 : 10
3х - 10 = -0,7
3х = 10 - 0,7
3х = 9,3
х = 9,3 : 3
х = 3,1
Проверка: 9 + 10 · (3 · 3,1 - 10) = 2
9 + 10 · (-0,7) = 2
9 + (-7) = 2
2 = 2
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
3) 7 + 9 · (4х + 5) = -2
9 · (4х + 5) = -2 - 7
9 · (4х + 5) = -9
4х + 5 = -9 : 9
4х + 5 = -1
4х = -1 - 5
4х = -6
х = -6 : 4
х = -1,5
Проверка: 7 + 9 · (4 · (-1,5) + 5) = -2
7 + 9 · (-1) = -2
7 - 9 = -2
-2 = -2
третье число х
первое число 2,4х
второе число х+0,6
сумма чисел 2,4*3=7,2
составим уравнение
х+2,4х+х+0,6=7,2
4,4х=7,2-0,6
4,4х=6,6
х=6,6:4,4
х=1,5 третье число
1,5*2,4=3,6 первое число
1,5+0,6=2,1 второе число
первое число х
второе число х+0,8
третье число 3,2х
сумма чисел 4,6*3=13,8
составим уравнение
х+х+3,2х=13,8-0,8
5,2х=13
х=13:5,2
х=2,5 первое число
2,5+0,8=3,3 второе число
2,5*3,2=8 третье число